Assessment of pathological response of breast cancer in patients undergoing neoadjuvant chemotherapy in a refferal hospital in Amazonas State - Pacheco, Kaiom Cesar Xavier; Pereira, Guilherme Vieira; Silva, Heitor Augusto de Magalhães e; Pereira, Henrique Vieira; Becil, Júlia Neves; Oliveira, Kimberly Farias de; Carvalho, Luana Izabela de Azevedo; Ribeiro, Márcio Henrique de Carvalho; Machado, Larissa Maria Contiero; Arruda, Lucas Barbosa; et al. (Mastology, 2024)
Introduction: The therapeutic options for breast cancer are diverse. Increasingly, treatments are established on an individual basis, depending on a series of variables ranging from age to the molecular profile of the tumor. When neoadjuvant chemotherapy (NAC) is necessary, adequate clinical evaluation (CE) and control examinations, such as breast ultrasound (US) and mammography (MMG), are of fundamental importance, as it is necessary to reevaluate the tumor lesion to determine an individualized surgical treatment, with the aim of performing breast-conserving surgery within the available techniques. This study sought to evaluate the pathological response of patients undergoing neoadjuvant chemotherapy, analyzing the presence or absence of tumor reduction by relating the physical examination with imaging methods (MMG and US), taking the anatomopathological examination measurements as the gold standard, thus intending to identify the best method for evaluating the pathological response. Methods: This was a prospective, observational, analytical cohort study. The study included 41 patients diagnosed with breast cancer detected by mammography and ultrasound (MMG and US) followed by biopsy, who underwent neoadjuvant chemotherapy (NAC) and surgery. The measurements of the malignant breast lesions obtained by CE, MMG and US were compared with the anatomopathological measurements on biopsy as the gold standard. Results: Pearson’s correlation coefficient was the statistical method used for evaluation, finding a value of 0.49 between the anatomopathological examination and CE, 0.47 between the anatomopathological examination and MMG and 0.48 between the anatomopathological examination and US (p<0.05). Conclusions: CE, MMG and US showed a moderate correlation with anatomopathological measurement, in addition to a moderate correlation between them, demonstrating equivalence in the pre-surgical definition of the size of the breast tumor after NAC, being complementary to each other to define a measure of greater accuracy of the tumor in breast cancer.